Cardiovascular Disease Risk Factors Profile Among Australian Vegetarian and Nonvegetarian Teenagers. Issue 3 (May 2021) - Grant, Ross; Pawlak, Roman; Vos, Paul; Bilgin, Ayse A.; Berg, Jade; Pearce, Robyn; Morris, Margaret
Atherosclerosis develops over a long period of time and often begins in childhood. The goal of this study was to make a cross-sectional assessment of the pattern of cardiovascular disease risk factors among Australian vegetarian (n = 49) and nonvegetarian (n = 639) 14- to 17-year-old participants from New South Wales, Australia. Vegetarians had statistically significant lower mean total (4.05 vs 4.4 mmol/L; P < .001) and low-density lipoprotein (LDL) cholesterol (2.18 vs 2.55 mmol/L; P < .001) and lower incidence of abnormal total and LDL cholesterol (31.1% vs 46.2%, P = .036, having total cholesterol ≥4.4 mmol/L and 13.3% vs 29.6%, P = .021, having LDL cholesterol ≥2.84 mmol/L). Vegetarians had a higher diastolic BP (72.0 vs 69.7 mm Hg; P = .038). No statistically significant difference was found in other risk factors including high-density lipoprotein cholesterol ( P = .83), triglycerides ( P = .601), systolic blood pressure ( P = .727), body mass index ( P = .159), plasma glucose ( P = .09), C-reactive protein ( P = .527), or homocysteine ( P = .45). The prevalence rate with 3 or more risk factors was 12.2% among vegetarians and 13.9% among nonvegetarians ( P = .156). The high percentage of abnormal total cholesterol in both diet groups and, in addition, LDL cholesterol in nonvegetarians is a cause of concern and underlines the need for lifestyle change.